Nitric oxide-based multi-synergistic nanomedicine: an emerging therapeutic for anticancer - Yaqin Tang; Qiyu Li; Ziwei Zhou; Huayang Bai; Nianting Xiao; Jing Xie; Chong Li (Journal of Nanobiotechnology)
Abstract Gas therapy has emerged as a promising approach for treating cancer, with gases like NO, H2S, and CO showing positive effects. Among these, NO is considered a key gas molecule with significant potential in stopping cancer progression. However, due to its high reactivity and short half-life, delivering NO directly to tumors is crucial for enhancing cancer treatment. NO-driven nanomedicines (NONs) have been developed to effectively deliver NO donors to tumors, showing great progress in recent years. This review provides an overview of the latest advancements in NO-based cancer nanotherapeutics. It discusses the types of NO donors used in current research, the mechanisms of action behind NO therapy for cancer, and the different delivery systems for NO donors in nanotherapeutics. It also explores the potential of combining NO donors with other treatments for enhanced cancer therapy. Finally, it examines the future prospects and challenges of using NONs in clinical settings for cancer treatment. Graphical Abstract